Thromboelastographic method for early decision on anticoagulant therapy in moderate to severe COVID-19 patients (Medical Journal of Indonesia, 2022)
BACKGROUND Coagulopathy is a serious COVID-19 complication that requires rapid diagnosis and anticoagulation. This study aimed to determine the role of coagulation examination using thromboelastography (TEG) on the decision-making time of anticoagulant therapy in COVID-19 patients and its clinical outcomes. METHODS A prospective observational study was conducted in Cipto Mangunkusumo Hospital, Indonesia, from October 2020 to March 2021. We consecutively recruited moderate and severe COVID-19 patients in the high and intensive care units. Turnaround time, time to anticoagulant therapy decision, and clinical outcomes (length of stay and 30-day mortality) were compared between those who had a TEG examination in addition to the standard coagulation profile examination (thrombocyte count, PT, APTT, D-dimer, and fibrinogen) and those who had only a standard coagulation profile laboratory examination. RESULTS Among 100 moderate to severe COVID-19 patients recruited, 50 patients had a TEG examination. The turnaround time of TEG was 45 (15–102) min versus 82 (19–164) min in the standard examination (p<0.001). The time to decision was significantly faster in the TEG group than the standard group (75 [42–133] min versus 184 [92–353] min, p<0.001). The turnaround time was positively correlated with time to decision (r = 0.760, p<0.001). However, TEG did not improve clinical outcomes such as length of stay (10.5 [3–20] versus 9 [2–39] days) and 30-day mortality (66% versus 64%). CONCLUSIONS The TEG method significantly enables quicker decision-making time for moderate to severe coagulation disorder in COVID-19 patients.